2022
DOI: 10.3389/fonc.2022.828852
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Response to Venetoclax and Decitabine in Acute Promyelocytic Leukemia With a Novel RARA-THRAP3 Fusion: A Case Report

Abstract: Variant acute promyelocytic leukemia (APL) showed quite different aspects, and the current treatments remained challenged at present. Venetoclax, a selective inhibitor of B-cell lymphoma 2 (BCL-2), is a small molecule that has been studied in several hematologic malignancies as both monotherapy and in combination with other agents. However, there is little of its use in the treatment of APL or variant APL. In this report, we identified THRAP3 as novel RARA fusion in resembling APL, which was resistant to all-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Interestingly, in the literature, we found several descriptions of APL cases with rare fusion genes that were treated with venetoclax. The positive fusion genes in these cases included STAT5B::RARA, HNRNPC::RARA, and THRAP3::RARA [13][14][15]. These special types of APL cases, with no CNS involvement, have also achieved good results.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, in the literature, we found several descriptions of APL cases with rare fusion genes that were treated with venetoclax. The positive fusion genes in these cases included STAT5B::RARA, HNRNPC::RARA, and THRAP3::RARA [13][14][15]. These special types of APL cases, with no CNS involvement, have also achieved good results.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, we found several cases treated with Venetoclax-based therapy: Liu et al 12 reported a novel HNRNPC-RARA fusion in variant APL who was sensitive to Venetoclax-based therapy. Song et al 13 identified THRAP3 as novel RARA fusion gene. This patient was salvaged by low-dose Venetoclax and decitabine.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sporadic case reports documented the successful treatment of ATRA/ATO‐resistant variant APLs with venetoclax monotherapy or in combination with chemotherapy (Table 1). 6–10 This is the first study to report on the efficacy and possible mechanisms of venetoclax plus ATRA regimen as a differentiation induction therapy in patients with variant APL carrying TNRC18::RARA . Venetoclax in combination with ATRA possesses advantages in terms of time to CR compared to venetoclax monotherapy and safety profiles compared to venetoclax‐based chemotherapy, especially suitable for older patients who are ineligible for intensive chemotherapy.…”
Section: Figurementioning
confidence: 98%